Scientific Computing in Electrical Engineering SCEE 2008 - Roos, Janne; Costa, Luis R.J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book is a collection of 65 selected papers presented at the 7th International Conference on Scientific Computing in Electrical Engineering (SCEE), held in Espoo, Finland, in 2008. The aim of the SCEE 2008 conference was to bring together scientists from academia and industry, e.g. mathematicians, electrical engineers, computer scientists, and physicists, with the goal of intensive discussions on industrially relevant mathematical problems, with an emphasis on modeling and numerical simulation of electronic circuits and devices, electromagnetic fields, and coupled problems.This extensive reference work is divided into five parts: 1. Computational electromagnetics, 2. Circuit simulation, 3. Coupled problems, 4. Mathematical and computational methods, and 5. Model-order reduction. Each part starts with an general introduction followed by the actual papers.
Part I Computational Electromagnetics -- Part II Circuit Simulation -- Part III Coupled Problems -- Part IV Mathematical and Computational Methods -- Part V Model-Order Reduction.
Keywords: Mathematics; Computer science -- Mathematics; Numerical analysis; Computer engineering; Mathematics; Computational Mathematics and Numerical Analysis; Electrical Engineering; Numerical Analysis